Advances of Endothelial Progenitor Cells in the Development of Depression - Yang, Nana; Sun, Shiyu; Duan, Guangqing; Lv, Kaixuan; Liang, Chen; Zhang, Linlin; Yu, Jielun; Tang, Yaohui; Lu, Guohua (Frontiers in Cellular Neuroscience, 2021)
Depression is a major psychological disease of human beings. With the severity of depression, it elevates the risk of cardiovascular disease (CVD), especially acute coronary syndrome (ACS), resulting in serious harm to human health. The number of endothelial progenitor cells (EPCs) is closely related to the development of depression. It has been reported that the number of peripheral blood EPCs in patients with depression was reduced. However, effects on the function of EPCs in depression are still unclear. This paper aims to analyze and summarize the research of EPCs in depression, and we envision that EPCs might act as a new target for evaluating the severity of depression and its complications.